APLIKASI SISTEM INFORMASI GEOGRAFIS PEMETAAN DIGITAL LOOP CARRIER - Lestari, Uning; -, Marwoto (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Currently Open Source software development takes place rapidly with a variety of variations. Support of many people towards Open Source software that is easy to come by, the main attraction that support poppularitas software. One of the Operating System that is popular among programmers in making Web-GIS is MapServer. Web-GIS a system that uses a computer device, to store, process, recall and manipulate geographic data. Using Geographic Information System (GIS) is expected for the users would be easier to know the mapping, GIS mapping for the location of the actual location can be described according to the conditions. MapServer is an example of a fairly successful operating system because it is supported by a community of loyal. By utilizing the Internet Geographic Information Systems Mapping Digital Loop Carrier can be applied using MapServer. Designing Web-GIS created using ArcView application assistance is very supportive in Web-GIS and mapping. Display Web-GIS on the Internet using MapServer and pemetaanya using ArcView, because ArcView is very supportive in the process of digitizing the map.